Ant interactions with native and exotic seeds in the Patagonian steppe: Influence of seed traits, disturbance levels and ant assemblage - Pirk, Gabriela Inés (2017)
Invasive plants may establish strong interactions with species in their new range which could limit or enhance their establishment and spread. These interactions depend upon traits of the invader and the recipient community, and may alter interactions among native species. In the Patagonian steppe we studied interactions of native ant assemblages with seeds of native and exotic plants, and asked whether ant–seed interactions differ with seed types and disturbance levels and whether the amount and type of ant–seed interactions can be predicted if both ant and seed traits are known. To characterize and quantify ant–seed interactions, we offered baits with large seeds of Pappostipa speciosa (native) and medium-sized elaiosome-bearing seeds of Carduus thoermeri (exotic), near and far from a road (high vs. low disturbed areas), and compared ant abundance and composition between areas. Interaction frequency was the highest for C. thoermeri seeds far from the road. Composition of ants interacting with C. thoermeri in these areas differed from that near the road and from that interacting with native seeds. Ant composition and abundance were similar between areas, but some species interacted more with exotic seeds in low disturbed areas. Ant foraging type predicted ant–seed interactions since the abundance of seed harvesters was positively correlated to interactions with P. speciosa, and that of generalists and predators, with interactions with C. thoermeri. The high interaction of ants with exotic seeds in low invaded areas suggests that ant activity could influence plant invasion, either by predating or dispersing seeds of invasive plants.